이질성 지수를 사용한 계절성 수요 예측모형 - 권순철 (The Graduate School, Ajou University, 2024)
As the domestic home appliance market in South Korea shifts towards online orders, the competition to meet customer demand with timely product delivery has intensified. Particularly for home appliances like residential air conditioners, refrigerators, washing machines, and large TVs, which require delivery and professional installation, providing differentiated and timely logistics services based on accurate demand forecasting has become crucial for business competitiveness. Additionally, with the recent need for same-day delivery and installation services, efficient Supply Chain Management (SCM) based on precise demand forecasting is more urgent than ever._x000D_ However, traditional seasonal forecasting models for products with clear seasonal demand, such as residential air conditioners during the summer, assume that the seasons start in January and last three months each. Recognizing that the actual start and duration of seasons can vary, this study develops a new model that enhances the accuracy of demand forecasting by introducing a ‘Heterogeneity Index’ for optimal seasonal segmentation, based on the Winter’s model. The effectiveness of this model is demonstrated through a case study on residential air conditioners.|최근 국내 가전제품 시장이 온라인 주문 중심으로 재편됨에 따라 고객의 수요에 맞춘 서비스 경쟁이 매우 치열해지고 있으며, 고객이 원하는 납기에 제품을 정확히 공급하는 역량이 더욱 중요 해졌다. 특히, 가정용 에어컨/냉장고/세탁기/대형 TV 등은 배달 및 전문설치 서비스가 수반되기 때문에 보다 정확한 수요예측에 기반한 설치 엔지니어 확보와 최적 배치로 차별화된 적기 배달설치 물류 서비스 제공이 비즈니스 경쟁력의 핵심이 된다. 더불어 시간 납기와 당일 배달설치 서비스까지 최근 Needs가 형성되고 있는 상황으로 정확한 수요예측에 기반한 SCM 운영이 시급한 시점이다. 그러나 여름철 수요가 집중되는 가정용 에어컨 등 계절성이 뚜렷한 가전제품의 수요를 예측하는 종전의 계절성 예측모형들은 계절이 1월에 시작하여 네 계절이 각각 3개월씩 지속된다고 가정한다. 그러나 현실은 각 계절의 시작월과 길이가 다를 수 있음에 착안하여, 본 연구에서는 윈터스 모델(Winter's model)을 기반으로 하면서도 최적의 계절 분할을 위한 '이질성 지수(Heterogeneity Index)'를 새롭게 고안하여 수요예측의 정확도를 높이는 모형을 개발하고, 가정용 에어컨을 사례로 그 성과를 실증 분석하였다.
학위논문(석사)--물류SCM학과,2024. 8
Keywords: Holt-Winters’ model; heterogeneity index; seasonal demand forecasting; 계절성 수요 예측; 윈터스 모델; 이질성 지수